Measles and Rubella - Arce, Julián (1920)
In the year just ended, have been observed in this capital, in addition to the epidemic outbreak of influenza, not happily reached considerable proportions that had the previous year (1918), an epidemic of measles and one rubella, which have developed simultaneously, Let's expose, on this occasion, some considerations on the latter two diseases, the clinical differentiation is often very difficult and often impossible.